Design and evaluation of a novel transdermal patch containing diclofenac and teriflunomide for rheumatoid arthritis therapy - Yuxiu Zhang; Dongmei Cun; Xin Kong; Liang Fang (Elsevier, 2014)
The aim of this study was to design a compound transdermal patch containing diclofenac (DA) and teriflunomide (TEF) for the treatment of rheumatoid arthritis (RA). The various organic amines salts of DA were prepared and their forming was confirmed using DSC and FTIR. The percutaneous permeation of organic amines salt of DA was investigated in vitro using a two-chamber diffusion cell with excised rabbit skin as transdermal barrier. The formulation of the patch was optimized in terms of the concentration of percutaneous permeation enhancer and the loading dose of drugs. The pharmacokinetic behavior of the optimal formulation was studies in rabbits and the anti-inflammatory and analgesic effects of the optimal patch were evaluated with the adjuvant arthritis model in rats and the pain model in mice, respectively. The result showed that skin penetration of diclofenac-triethylamine (DA-TEtA) salt was better than other organic amine salts. Based on previous study of our laboratory, teriflunomide-triethylamine (TEF-TEtA) significantly enhanced the skin permeation of TEF. 10% of azone (AZ) was the best enhancer for the two drugs. The optimal patch formulation was composed of 2% of TEF-TEtA, 6% of DA-TEtA and 10% of AZ. The cumulative permeated amount of DA-TEtA in vitro was comparable with that of the commercial diclofenac-diethylamine (DA-DEtA) patch. The absolute bioavailability of TEF-TEtA was 42%, which could achieve the therapeutic drug levels. In animal study, the optimized compound patch containing DA-TEtA and TEF-TEtA displayed significant anti-inflammatory and analgesic effect, which indicated the potential of the compound patch.